Impactos del actual programa de transferencia del manejo de la irrigacion en Colombia. In SpanishImpacts of Colombia's current irrigation management transfer program - Vermillion, Douglas L.; Restrepo, C.G. (International Water Management Institute, 1998)
Assess the impacts of the current national irrigation management transfer program in Colombia. Examines the context of transfer, the basic transfer strategy, the impacts of transfer, and the powers and functions devolved in the transferred districts. The need to use the transfer process to create local management self-reliance is also stressed.